2016
DOI: 10.1016/j.indcrop.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical hydrogen and methane potential of sugarcane syrup using a two-stage anaerobic fermentation process

Abstract: The potential of using a two-stage hydrogen and methane fermentation of sugarcane juice was studied. The effects of pure and mixed culture as inocula on hydrogen production were compared. Additionally, the effects of pure culture inocula form, i.e., free cells or immobilized cells of Clostridium butyricum TISTR1032 was compared to different forms of mixed cultures, i.e., granules or suspended cells of heat-treated upflow anaerobic sludge blanket (UASB) granules. The hydrogenogenic effluents from all treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…However, no LAB was detected in the mixed enzymes. The findings were consistent with our previous reports [60,61] that the anaerobic granules collected from the anaerobic digester at Khon Kaen Brewery Co., Ltd., Khon Kaen, Thailand contained Lactobacillus spp. The presence of LAB was considered adverse as, aside from their competitive consumption of substrate, lactic acid can lower the pH of a fermentation broth, leading to unfavorable conditions for hydrogen synthesis [62].…”
Section: Effect Of Initial Biomass Concentration On Hydrogen Productisupporting
confidence: 93%
“…However, no LAB was detected in the mixed enzymes. The findings were consistent with our previous reports [60,61] that the anaerobic granules collected from the anaerobic digester at Khon Kaen Brewery Co., Ltd., Khon Kaen, Thailand contained Lactobacillus spp. The presence of LAB was considered adverse as, aside from their competitive consumption of substrate, lactic acid can lower the pH of a fermentation broth, leading to unfavorable conditions for hydrogen synthesis [62].…”
Section: Effect Of Initial Biomass Concentration On Hydrogen Productisupporting
confidence: 93%
“…Consequently, more HP and HY were obtained (Table 1). In addition, C. butyricum is a well known hydrogen producer and has been reported to show the ability to utilize various kinds of substrates such as glucose [41], sugarcane syrup [41,42] and lignocellulosic biomass [43]. The concentration of soluble metabolite products (SMPs) in the fermentation broth with C. butyricum were higher than that without C. butyricum.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were centrifuged at 10,000 rpm for 5 min in order to precipitate the suspended microbes. The cell pellets were collected and kept in 50% sterile glycerol at −20 °C prior to microbial community analysis [7] by PCR-DGGE following the method of Kongjan et al (2011) [57]. Most of the bands were excised from the gel and re-amplified.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Cater et al [4] reported a successful use of cocultures of Pseudobutyrivibrio xylanivorans Mz5 (T) and Fibrobacter succinogenes S85 and co-culture of Clostridium cellulovorans and Fibrobacter succinogenes S85 for methane production from brewery spent grain. In addition, the use of mixed cultures such as sewage sludge [5], anaerobic digested sludge [6], upflow anaerobic sludge blanket (UASB) granules [7] and activated sludge [8,9] were found to enhance biogas production. Based on this information, an addition of inocula or bioaugmentation technique is a promising approach to enhance the AD process.…”
Section: Introductionmentioning
confidence: 99%